2021
DOI: 10.1007/s00268-021-06051-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Inflammatory Biomarkers in 5‐Year Survival After Endovascular Repair of Abdominal Aortic Aneurysms in a Predominantly Male Cohort: Implications for Practice

Abstract: Background Prognostic factors of long-term survival can guide selection of patients for endovascular repair of abdominal aortic aneurysms (EVAR). The aim of this study was to evaluate the relationship between the neutrophilto-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR), the lymphocyte-to-monocyte ratio (LMR) and the systemic immune-inflammation index (SIII) with survival after EVAR and to assess whether the addition of these biomarkers improved the prediction of survival after surgery. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…One study showed a linear relationship between survival and NLR, PLR, and LMR, but found an independent relationship between survival and NLR but not PLR or LMR. 18 Our data shows that a low preoperative LMR of <3.21 independently predicts overall mortality after EVAR for AAA (Table 2). This cut-off value is comparable to previously reported values for cancer patients (median 3.0, range 2.0-5.3).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…One study showed a linear relationship between survival and NLR, PLR, and LMR, but found an independent relationship between survival and NLR but not PLR or LMR. 18 Our data shows that a low preoperative LMR of <3.21 independently predicts overall mortality after EVAR for AAA (Table 2). This cut-off value is comparable to previously reported values for cancer patients (median 3.0, range 2.0-5.3).…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies, including ours, showed that a high neutrophil-to-lymphocyte ratio (NLR) is associated with poor long-term survival in patients undergoing EVAR for AAA. [2][3][4][5] The NLR of >3.0 to 4.0 was associated with increased mortality after elective EVAR, regardless of other comorbidities. Neutrophilia is associated with trauma, stress, bacterial infection, and cancer, any of which ultimately might increase the risk of death from any cause.…”
Section: Introductionmentioning
confidence: 97%
“…However, the mediation effect of the PLR between ondansetron use and 28‐day mortality was not observed. In a study of patients who had undergone endovascular repair of abdominal aortic aneurysms, the NLR and PLR were linear and associated independently with their survival, but the NLR (not the PLR) moderately improved the prediction of survival score 44 . In one study on COVID‐19, the NLR (not the PLR) could be considered an independent biomarker for indicating a poor clinical outcome 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients who had undergone endovascular repair of abdominal aortic aneurysms, the NLR and PLR were linear and associated independently with their survival, but the NLR (not the PLR) moderately improved the prediction of survival score. 44 In one study on COVID-19, the NLR (not the PLR) could be considered an independent biomarker for indicating a poor clinical outcome. 45 Hence, from the aspect of predicting survival from a critical illness, the PLR may not be as valuable as the NLR.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has been proven to be associated with the perioperative morbidity of ruptured AAA and mortality after selective EVAR [ 24 , 25 ]. However, the correlation between novel SIMs and the long-term survival rates after EVAR remains uncertain.…”
Section: Introductionmentioning
confidence: 99%